The Effectiveness of an educational program based on the activities of mathematics in the educational achievement of pupils in the third grade. (Semi-experimental study in the city of Latakia) - Nassour, Raghda; Ghosoun, Samah (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to study the effectiveness of an educational program based on the entertaining mathematics activities and its effect on improving mathematics achievement in sample of 60 pupils, divided into two groups: experimental and control groups. The researcher applied an educational program based on entertaining activities the experimental group, while the experimental group learned through the usual method. She prepared the study achievement, then she collected the data and analyzed it. The reached the following results: 1. There is no statistically significant difference the level 0.5% between the average scores of pupils marks in experimental and control group the improving of educational achievement. 2. The effectiveness entertaining activities in improving the achievement the third grade pupils in mathematics. Search has ended with a collection of suggestions only for conferences activities in learning mathematics.